A fuzzy logic based approach to linguistic summaries of databases - Kacprzyk, Janusz (1947- ); Yager, Ronald R.; Zadrożny, Sławomir (Zielona Góra: Uniwersytet Zielonogórski)
This paper, we present basic ideas and perspectives related to the use of fuzzy logic for the derivation of linguistic summaries of data (databases). We concentrate on the issue of how to measure the goodness of a linguistic summary, and on how to embed data summarization within the fuzzy querying environment, for an effective and efficient implementation.
Keywords: fuzzy logic; linguistic summary; computing with words; data mining; fuzzy querying